Identifying Key Imperatives of Corporate Entrepreneurship at Technology-based Firms in Taiwan - Chang, Yun-Chien (2009)
The paper is inspired by the dilemma facing the technology-based companies in Taiwan, which are the main source of GDP. The aim of this study is to clearly identify the factors that drive the business to success or failure through reviewing the corporate entrepreneurship within three representative organisations, in which the research firstly distinguishes established firms by organisation size. Therefore, the evaluation of corporate venturing would be shown by a cross comparison between mid-sized and large firms. At the end, the paper concludes that in the context of high technology industry in Taiwan, firms should focus on two imperatives of corporate entrepreneurship, which are technology development and customer type consistently.